A retomada da retomada: o trabalho da memória das mulheres Xokó - Silva, Ana Carolina de Assis Marinho da (2024)
By returning to memories of the period of struggle for the Xokó indigenous territory, women highlight new characters, modes of existence, performances and memory in the collective narrative. As in a process of retaking the retakings, other narratives take shape in this oraliture. Anchored in the work of the memory of the struggle for land, intertwining ethnographic and documentary research - with audiovisual production as interlocutor support - this study emerges at the intersection between gender and the construction of collective memory, in addition to understanding forms of resistance and protagonism of women, from within of the Xokó narratives. From the work of female memory it was possible to identify areas of activity headed by them: economic, educational, magicalreligious and cultural. These are areas that dialogue and intersect. Therefore, we will understand that by narrating their own memories, women regain their leading role in history and subvert the pressures of invisibilization policies, not only regarding gender, but also regarding the indigenous collective as a whole.